Critical limits of zinc in soil and rice plant grown in alluvial soils of West Bengal, India (SAARC Journal of Agriculture, 2014)
A study was conducted in 22 alluvial soils of West Bengal, India to estimate the critical limit of Zn in soil and rice plant for predicting the response of rice (Oryza sativa) to zinc application. The DTPA-extractable Zn was positively and significantly correlated with CEC, organic carbon and clay contents and negatively correlated with pH, silt and sand contents of soil. The DTPA-extractable Zn also showed a positive correlation with dry matter yield and plant Zn content. The critical concentration of Zn in these soils was established at 0.75 mg kg-1 for rice and that of 28.0 mg kg-1 in the plant tissue. Soil containing Zn below the critical limit responded appreciably to Zn fertilization. A negative response to Zn application was also observed at its higher level. The average dry matter yield increases with increasing level of Zn application up to 2.5 mg kg-1 in Zn deficient soils. The average response to Zn application in rice in Zn deficient soils was found to be 68.5% and 19.9% in Zn adequate soils. DOI: http://dx.doi.org/10.3329/sja.v10i2.18334 SAARC J. Agri., 10(2): 137-146 (2012)